Assessing the Hazard of Metals and Inorganic Metal Substances in Aquatic and Terrestrial Systems - Adams, William (CRC Press, 2009)
Current procedures used for hazard identification and classification are based on persistence, bioaccumulation, and toxicity measurements. Assessing the Hazard of Metals and Inorganic Metal Substances in Aquatic and Terrestrial Systems provides the basis for improvements to the current model for hazard assessment. The book reviews the scientific underpinnings of the use of persistence as applied to metals, including bioavailability, and the use of bioaccumulation to evaluate aquatic species and aquatic-linked food chains. It also examines toxicity procedures as used within PBT approaches and measurements for metals in terrestrial ecosystems.